2014
DOI: 10.1186/1471-2164-15-1167
|View full text |Cite
|
Sign up to set email alerts
|

Proteome changes underpin improved meat quality and yield of chickens (Gallus gallus) fed the probiotic Enterococcus faecium

Abstract: BackgroundSupplementation of broiler chicken diets with probiotics may improve carcass characteristics and meat quality. However, the underlying molecular mechanism remains unclear. In the present study, 2D-DIGE-based proteomics was employed to investigate the proteome changes associated with improved carcass traits and meat quality of Arbor Acres broilers (Gallus gallus) fed the probiotic Enterococcus faecium.ResultsThe probiotic significantly increased meat colour, water holding capacity and pH of pectoral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 83 publications
2
51
1
Order By: Relevance
“…Zamanzad-Ghavidel et al (2011) reported that relative breast meat in chickens fed a diet containing Lactobacillus-based probiotic was higher than in those that did not receive the probiotic, consistent with the findings of the current study. Also Zheng et al (2015) reported that feeding broiler chickens diets containing Enterococcus faecium led to a significant improvement in breast muscle yield. They suggested that the main effects of Enterococcus faecium occur in the intestine through modulation of the intestinal microbiota in favour of the host animal and through improved mucosa ultrastructure, enhanced nutrient absorption and reduced energy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Zamanzad-Ghavidel et al (2011) reported that relative breast meat in chickens fed a diet containing Lactobacillus-based probiotic was higher than in those that did not receive the probiotic, consistent with the findings of the current study. Also Zheng et al (2015) reported that feeding broiler chickens diets containing Enterococcus faecium led to a significant improvement in breast muscle yield. They suggested that the main effects of Enterococcus faecium occur in the intestine through modulation of the intestinal microbiota in favour of the host animal and through improved mucosa ultrastructure, enhanced nutrient absorption and reduced energy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen Free Chickens quality, including Clostridium butyricum in pigs (Meng et al, 2010) and Bacillus coagulans , Bacillus subtilis (Fan et al, 2013;Park and Kim, 2014), Enterococcus faecium (Zheng et al, 2014), L. plantarum (Loh et al, 2013) and Rhodopseudomonas palustris (Xu et al, 2014) in chickens. These results showed a lot of different indicators of the effects of probiotics on meat quality (Suo et al, 2012).…”
Section: Isolation and Probiotic Potential Of Lactobacillus Salivariumentioning
confidence: 99%
“…Meng et al (2010) demonstrated that the probiotic treatment groups had increased meat color scores, marbling scores, and redness values in growingfinishing pigs. Until now, the functioning mechanism of probiotics (especially Lactobacillus) on meat quality (fat content in the study) remains unclear, although some investigators have attributed the effects of probiotics on meat quality to the role of bacteriocins or extracts (Zheng et al, 2014). We considered that further study of the effects of L. salivarius and P. pentosaceus on meat quality was required.…”
Section: Isolation and Probiotic Potential Of Lactobacillus Salivariumentioning
confidence: 99%
“…Aksu et al (2005) reported that dietary supplementation of 0.2% Saccharomyces cerevisiae increased pH of chicken breast muscle, from 6.24 to 6.31. A recent study conducted by Zheng et al (2015) found that breast muscle (6.11) from chickens fed Enterococcus faecium had higher ultimate pH value than that from control without probiotic feeding (5.77), in which downregulation of glycolytic enzymes such as β-enolase and pyruvate kinase muscle isozyme was suggested as a possible cause for the high pH in breast muscle from chicken fed the probiotic. Therefore, the observed high ultimate pH of breast muscle from probiotic groups in the current study might be related to the down-regulating effect of probiotic supplementation on glycolytic enzymes that could alleviate an increase in glycolytic metabolism induced by high ambient temperature.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it was suggested that the decreased ultimate pH could be associated with poor quality characteristic of breast muscle from chronic heat-stressed broilers, particularly on color, WHC, and tenderness (Zhang et al, 2012). Some previous studies have found that microbial probiotic supplementation could increase ultimate pH of chicken breast muscle (Pelicano et al, 2003;Aksu et al, 2005;Zheng et al, 2015). Aksu et al (2005) reported that dietary supplementation of 0.2% Saccharomyces cerevisiae increased pH of chicken breast muscle, from 6.24 to 6.31.…”
Section: Discussionmentioning
confidence: 99%